TRANSFORMATIVE LEADERSHIP MANAGEMENT DEVELOPING GEN-Z CHARACTER INTEGRITY (CASE STUDY AT DAARUT TAUHIID ISLAMIC BOARDING SCHOOL, BANDUNG) - Rohima, Yulia Kuraesin Ila; Wulan, Sri; Sabarudin, Mohammad; Rahmat, Rahmat; Badrudin, Badrudin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The purpose of this study is to analyze and understand the managerial transformational leadership in developing the character of students with integrity. Islamic boarding schools as traditional Islamic educational institutions face the challenges of modernization that cannot be separated from the role of charismatic leaders who are able to adapt to the development of the times. The research method uses an exploratory qualitative approach with a case study at the Daarut Tauhiid Islamic Boarding School in Bandung, West Java, Indonesia. Data were collected through direct observation, documentation studies, and interviews with the management leaders of the foundation, staff, students, and alumni of students. The results of the study indicate that transformational leadership management includes exemplary behavior, caring, creativity, communication, and adaptive to technology. The combination of charismatic-transformative leadership styles focuses on technology-based humanism, adaptive to change, strengthening skills, and commitment to continuous learning. This study complements previous literature and offers a new design of transformative leadership that stimulates the emergence of great works of students, in order to realize Daarut Tauhiid as one of the Religious Tourism Areas and Centers of Islamic Civilization in Indonesia based on modern technology with a character of integrity.